2008
DOI: 10.1097/iop.0b013e3181853645
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Dysplasia-like Tumor of the Lacrimal Sac

Abstract: A 75-year-old woman developed epiphora and a slowly enlarging right medial canthal mass for 1 year. CT revealed a mass with ground-glass radiodensity and hazy borders in the lacrimal sac. At external dacryocystorhinostomy, a tan, gritty, spherical mass was easily removed from the sac lumen. Histopathologic characteristics were typical of fibrous dysplasia. The postoperative course was uneventful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, no relevant studies on the subject have been reported in the literature to date. [1][2][3][4][5][6] Knowledge of the osseous appearance in this region could help radiologists and clinicians increase their awareness of the variant or asymptomatic FD, avoiding confusion with tumor or infection. For us, there has been some recent interest in the appearance of the frontal process of the maxilla.…”
mentioning
confidence: 99%
“…To the best of our knowledge, no relevant studies on the subject have been reported in the literature to date. [1][2][3][4][5][6] Knowledge of the osseous appearance in this region could help radiologists and clinicians increase their awareness of the variant or asymptomatic FD, avoiding confusion with tumor or infection. For us, there has been some recent interest in the appearance of the frontal process of the maxilla.…”
mentioning
confidence: 99%